An interviewwith Elisabeth Hsu on Plants, Health and Healing: On the Interface of Ethnobotany and Medical Anthropology - Sofia A. Vougioukalou (Ethnobiology Letters, 2012)
In this interview Professor Elisabeth Hsu discusses ethnobiology as an interdisciplinary science and introduces the book she co-edited with Dr. Stephen Harris Plants, Health and Healing: On the Interface of Ethnobotany and Medical Anthropology (Hsu and Harris 2010). She discusses epistemological contradictions between biologically and anthropologically orientated ethnobiological studies and argues for a more anthropologically grounded and methodologically rigorous discipline. The interview took place at the School of Anthropology and Conservation at the University of Kent in the UK in February 2011.